2010
DOI: 10.4028/www.scientific.net/msf.654-656.2572
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Physical Properties of Ti-Coated Diamond/Al Composites Prepared by Pressure Infiltration

Abstract: Thermo-physical properties of diamond reinforced Al composites were investigated. Volume fraction of diamond particles was up to 55%. In order to improve the interfacial bonding between diamond and aluminum, diamond particles were pre-coated with titanium using molten salt method. XRD and SEM observation showed that the Ti coating on diamond consists of carbide layer and metal layer, which mainly depend on temperature and time. The influences of the Ti coating on interfacial characteristic and the thermo-physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…This δ-TiC transition layer combines metallurgically with diamond, and the outer α-Ti layer remains on the outer surface. Upon the addition of Ti-coated diamond to the Al alloy matrix, the outer α-Ti later enables the wetting of the Al alloy matrix [61]. As a result, the Al3Ti phase was formed around the temperature of 590 °C [62,63], as evident from the XRD peaks at 38.46° and 64.56°, as shown in Figure 5; similar peaks were observed in other research works [58].…”
Section: Microstructural Analysissupporting
confidence: 79%
“…This δ-TiC transition layer combines metallurgically with diamond, and the outer α-Ti layer remains on the outer surface. Upon the addition of Ti-coated diamond to the Al alloy matrix, the outer α-Ti later enables the wetting of the Al alloy matrix [61]. As a result, the Al3Ti phase was formed around the temperature of 590 °C [62,63], as evident from the XRD peaks at 38.46° and 64.56°, as shown in Figure 5; similar peaks were observed in other research works [58].…”
Section: Microstructural Analysissupporting
confidence: 79%
“…Johnson and Sonuparlak, (1993) studied SiC coated diamond particles and showed that increasing thickness of the SiC coating leads to lower CTE's. Zhang, Shen, and Tong (2010) studied the influences of the Ti coating on interfacial characteristic and the thermo-physical properties of diamond reinforced aluminum with volume fraction of diamond particles up to 55%. They observed increase of TC of the composites up to 430 W/mK and CTE up to 6.40 ·10 −6 1/K.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] However, because of their poor wettability, D and metal are difficult to obtain a strong interface bonding, making it difficult to improve the properties of composites. [10] Therefore, to improve the performance of composites, it is necessary to improve the interface bonding state between D and metal. At DOI: 10.1002/crat.202200258 present, researchers have introduced coatings (Ti, W, Cr, TiC, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…And the thermal conductivity of copper matrix composites was improved by about 43%. Zhang [10] et al used the NaCl-KCl molten salt method to prepare the TiC coating on the D surface at 800 °C, which improved the thermal conductivity of aluminum matrix composites by 115%. To obtain a better and more controllable TiC coating, Li [30] et al studied in detail the influence of molten salt type and temperature on TiC coating on carbon fibers surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation